Combining Language Corpora With Experimental and Computational Approaches for Language Acquisition Research. (14th December 2016) - Monaghan, Padraic; Rowland, Caroline F.
Abstract : Historically, first language acquisition research was a painstaking process of observation, requiring the laborious hand coding of children's linguistic productions, followed by the generation of abstract theoretical proposals for how the developmental process unfolds. Recently, the ability to collect large‐scale corpora of children's language exposure has revolutionized the field. New techniques enable more precise measurements of children's actual language input, and these corpora constrain computational and cognitive theories of language development, which can then generate predictions about learning behavior. We describe several instances where corpus, computational, and experimental work have been productively combined to uncover the first language acquisition process and the richness of multimodal properties of the environment, highlighting how these methods can be extended to address related issues in second language research. Finally, we outline some of the difficulties that can be encountered when applying multimethod approaches and show how these difficulties can be obviated.